Usability of a home-based test for the measurement of fecal calprotectin in asymptomatic IBD patients. Issue 9 (September 2017) - Bello, Caroline; Roseth, Arne; Guardiola, Jordi; Reenaers, Catherine; Ruiz-Cerulla, Alexandra; Van Kemseke, Catherine; Arajol, Claudia; Reinhard, Christian; Seidel, Laurence; Louis, Edouard
Abstract: The aim of our work was to test the usability of fecal calprotectin (FC) home-based test in inflammatory bowel disease (IBD) patients. Methods: IBD patients were prospectively recruited. They had to measure FC with a dedicated tool and smartphone application, 5 times at two weeks intervals over an 8 weeks period. They had to fill in a usability questionnaire at the first and the last FC measurement. A System Usability Scale (SUS: 0–100) and the Global Score of Usability (GSU: 0–85) were calculated. FC was also centrally measured by ELISA. Results: Fifty-eight patients were recruited. Forty-two performed at least one FC measurement and 27 performed all the FC requested measurements. The median (IQR) SUS (0–100) at the first and last use were 85 (78–90) and 81 (70–88), respectively; the median (IQR) GSU (0–85) at the first and last use were 74 (69–80) and 77 (68–83), respectively. Adherence to the planned measurements and usability of the tool were higher in females and in less severe disease. The intra-class correlation coefficient between home-based and centrally measured FC was 0.88. Conclusion: The adherence to home-based measurement of FC was fair. Usability scores for the home-based test were high. There was a good correlation with the centrally measured FC by ELISA.